POTENTIAL OF VIRGIN COCONUT OIL PASTE AS EXTRINSIC DENTAL STAIN REMOVAL - Khusnul Munika Listari; Siham (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: Dental stain is a common condition in society, apart from being an aesthetic problem it can be a predisposing factor for periodontal disease.One type of dental stain is extrinsic dental stain. Virgin Coconut Oil contains lauric acid which has the potential to remove extrinsic dental stains through the foaming mechanism. This research is to determine the effectiveness of Virgin Coconut Oil paste on removing extrinsic dental stain through an in vitro study. Material and Methods: Twenty-five post extraction premolars with extrinsic dental stain on buccal area were divided into 5 groups that is : K1/Control(given artificial saliva), K2(given placebo paste), K3(given 50% Virgin Coconut Oil paste), K4(given 75% Coconut Oil Paste) and K5(given 100% Virgin Coconut Oil Paste). Difference colour intensity (ΔE) before and after treatment were observed using Adobe Photoshop CC 2018 in the CieLAB system. Results and Discussion: Data were analyzed using One Way ANOVA and Post-Hoc Multiple Comparison test. One Way ANOVA test showed that there were significant differences within groups (p<0.05). Post-Hoc Multiple Comparison test showed that there were significant differences between each groups, except for K2 and K3 groups also K4 and K5 groups (P>0.05). Conclusion: Virgin Coconut Oil Paste is effective on removing extrinsic dental stain in vitro